The Icelandic preposition hjá ‘at’: Its role in canonical intransitive sentences - Yamaguchi, Toshiko (Journal of Modern Languages, 2017)
This paper seeks to explain the roles that the preposition hjá plays in canonical intransitive sentences in Icelandic. According to Hopper and Thompson’s (1980) transitivity hypothesis, this type of intransitive sentence is characterised by the expression of an event that contains a participant affected by that event. The Icelandic intransitive sentence designates a change of state, agentivity, and a resultant state. The third meaning is particularly important as it expresses a situation that is not necessarily part of the meaning of the predicate but rather evoked by the speaker’s real-world knowledge. The addition of hjá makes the intransitive sentence more transitive because it gives rise to an additional participant. The key to understanding the unique behaviour of hjá is to decode its semantic and pragmatic, or conceptual, properties. The entire issue ultimately comes down to two fundamental questions: how do we perceive the world and how is it coded in a language?